Photo-reduction of silver salts on highly heterogeneous lead zirconate titanate - Jones, Paul M.; Dunn, Steve (Institute of Physics (IOP), 2007)
This paper presents the work undertaken to determine the influences on the photo-induced growth of silver nanoclusters on the surfaces of lead zirconate titanate thin films. The lead zirconate titanate films were grown on indium tin oxide coated glass. They exhibited a highly textured surface and can be treated as wide bandgap semiconductors that exhibit ferroelectric behaviour. We show that there is a preferential deposition of silver metal on the ferroelectric films that is related not only to the polarization state of the ferroelectric domains but also to the surface defects such as grain boundaries and defects within the film. The greatest deposition rates are found to occur at grain boundaries where there is an approximately 40:1 ratio of silver clusters when compared to the native positive domains exhibited by the lead zirconate titanate. We propose that the mechanism for cluster growth depends on the availability, and diffusion rate, of electrons into the growing cluster and that the clusters grow from a discrete nucleation point. We also show that the growth of a monolayer of silver is sufficient to prevent the formation of electron–hole pairs by blocking the UV irradiation and that the silver nanoparticles are readily removed from the surface using an ultrasonic bath leading to a possible new method of manufacturing metal nanoparticles.